THE WHITE WOMAN’S SYMPATHY AND BLACK WOMEN RESISTANCE IN THE TATE TAYLOR THE HELP FILM - Syafik, Azzahra; Syam, Essy; Edward,; Hutahaean, Sorta (Elite : English and Literature Journal, 2023)
This qualitative research discusses black women's resistance and white women's sympathy in The Help film. In the main theory, this research uses Scott's resistance theory, which consists of close Resistance, semi-open resistance, and open resistance. The data in this research includes dialogue and scenes from The Help film, which describe black women's resistance and white women's sympathy. In obtaining the data, this research uses observation by watching the dialogue about black women's resistance and white women's sympathy and documentation by saving this dialogue and scenes from this film. The data in this research is repeatedly analyzed by the interactive technique, which consists of three steps: data reduction in selecting the representative data, data display in creating the table, and data conclusion in concluding the data analysis. This research shows that black women resist white superiority by talking to white women about white people's mistreatment, defending themselves from white people's accusations, and taking revenge on white women. Besides, white women sympathize with black women by writing a book about the black maid, feeling empathy and sorry for the back maid, and taking revenge for black maids.